2021
DOI: 10.26603/001c.21317
|View full text |Cite
|
Sign up to set email alerts
|

The Single Leg Squat Test: A “Top-Down” or “Bottom-Up” Functional Performance Test?

Abstract: Background Medial knee deviation (MKD) during the single leg squat test (SLST) is a common clinical finding that is often attributed to impairments of proximal muscular structures. Investigations into the relationship between MKD and the foot and ankle complex have provided conflicting results, which may impact clinicians’ interpretation of the SLST. Purpose The purpose of this study was to compare ankle dorsiflexion range of motion (ROM) and foot posture in subjects th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…However, findings related to more dynamic tasks such as the LS may be more useful for understanding acute injuries and their rehabilitation, as dynamic tasks account for a greater proportion of acute injury mechanisms 25 26 . This is particularly true at the tibiofemoral joint, as the pivot shift mechanism (the most prominent theory for ACL injury mechanism) is comprised of movement in the two (frontal and transverse) planes demonstrated in this present study to be most affected by higher level cognitive dual-tasking such as SS 27 28 . Future work should aim to simulate real-world conditions as well as sport-specific conditions using dual-tasking to study the effects of cognitive-motor interference on lower extremity injuries as well as investigate baseline performance on dual task assessments and prospectively monitor athletes over a season of play for injury incidence.…”
Section: Discussionmentioning
confidence: 73%
“…However, findings related to more dynamic tasks such as the LS may be more useful for understanding acute injuries and their rehabilitation, as dynamic tasks account for a greater proportion of acute injury mechanisms 25 26 . This is particularly true at the tibiofemoral joint, as the pivot shift mechanism (the most prominent theory for ACL injury mechanism) is comprised of movement in the two (frontal and transverse) planes demonstrated in this present study to be most affected by higher level cognitive dual-tasking such as SS 27 28 . Future work should aim to simulate real-world conditions as well as sport-specific conditions using dual-tasking to study the effects of cognitive-motor interference on lower extremity injuries as well as investigate baseline performance on dual task assessments and prospectively monitor athletes over a season of play for injury incidence.…”
Section: Discussionmentioning
confidence: 73%
“…This may be the reason why no significant correlation was found between head and trunk motions in the sagittal plane in the current study. This study found correlations only in the sagittal and frontal planes because a systematic review found low validity for the rotation components of the trunk and lower limb joints [49], and trunk lateral leaning in the frontal plane has commonly been considered as the target movement that needs to be detected during rehabilitation exercise in previous studies rather than sagittal and transverse planes in people with pain in the lower back, knee, and ankle [33,42,50,51]. However, another study reported that runners who performed single-leg squats poorly had excessive trunk rotation in the transverse plane towards the stance limb [52], indicating the need to measure motion with three degrees of freedom using wearable sensors in the future study.…”
Section: Pairwise Correlations Between Head Angle and Angles Of Other Jointsmentioning
confidence: 93%
“…An earbud IMU sensor could be used for measuring the trunk motion indirectly in clinical and sports settings. Specifically, earbud IMU sensors can be used to prevent knee injury by assessing frontal trunk motion during functional performance tests, such as single-leg squats and forward step-down tests, because frontal trunk motions can directly influence the knee moment in the frontal plane; people with knee pain reportedly exhibited greater ipsilateral trunk lean than did healthy controls [33,42]. An earbud IMU sensor can also provide real-time music-based feedback for effective training to reduce excessive trunk lateral lean while contracting weak hip muscles for knee rehabilitation because excessive trunk lateral lean means poorer hip abductor and external rotator function during workout activities (single-leg squats, lunges, and standing hip abduction) [33]; for example, music played through the wireless earbud during a workout could be distorted if trunk lateral lean occurs during single-leg squats and lunges.…”
Section: Pairwise Correlations Between Head Angle and Angles Of Other Jointsmentioning
confidence: 99%
“…11,12 Because the step-down test may place a greater emphasis on ankle motion, it may be a better measure than the single leg squat test in those with foot and ankle pathologies. 13 Compensatory lower extremity movements can be identified and characterized as being associated with abnormal pronation or supination during gait and functional movement assessment. Physical therapists may use the general characteristics associated abnormal pronation or abnormal supination to describe the movement system disorder and serve as a guide for evaluating and managing athletes with common forefoot pathologies such as stress fractures, metatarsalgia, neuroma, and sesamoiditis.…”
Section: Biomechanical Considerationsmentioning
confidence: 99%